PEMBUATAN MODUL INTERAKTIF TERINTEGRASI GUIDED INQUIRY MENGGUNAKAN APLIKASI COURSE LAB UNTUK MATERI USAHA, ENERGI, MOMENTUM DAN IMPULS PADA PEMBELAJARAN FISIKA SMA KELAS X - Ahmad Dedi Putra; Murtiani Murtiani; Gusnedi Gusnedi (PILLAR OF PHYSICS EDUCATION, 2017)
Learning resources used by educators in schools in the process of physics learning is still not capable of making learners become more active and independent in the learning process. Learning resources used were still in the form of regular print books and not interactive so that learning will be monotonous, learners less motivated and lazy to do the task given. The solution to this problem was to use an interactive module that has been designed. This research aimed to produce integrated interactive module guided inquiry using course lab application for business material, energy, momentum and impulse at Class X high school physics learning which is valid and practical. This research was a research development using R & D model Sugiyono. This model consiststed of 10 stages, but the research is only up to seven stages: knowing potentials and problems, gathering information, designing products, validating designs, revising designs, testing products, and revising products. Research subjects in this research are 3 validators to know the value of product validity, 2 educators, and learners in a class X SMA 6 Kerinci to know the practical value of the product. Data were analyzed by descriptive analysis technique. Based on the research which had been done, the product was produced in the form of interactive module. The research product was at very valid criterion with mean value 88,44% covering content validation aspect, presentation, graphical, and linguistic. The research product was at very practical criteria by educators with an average score of 90.77% which includes aspects of ease of use, efficiency of learning time, and benefits. The research product was also in very practical criteria by learners with an average value of 90.33% which includes aspects of ease of use of the menu, ease of use guidance, the use of multimedia, and motivation learners